1990
DOI: 10.1002/hep.1840110417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streptozotocin diabetes in the rat on blood levels of ten specific plasma proteins and on their net biosynthesis by the isolated perfused liver

Abstract: Adult male Sprague-Dawley rats with streptozotocin-induced diabetes (6 to 8 wk duration), treated or untreated with insulin, were studied with two aims: (a) to ascertain whether protracted diabetes in the rat is associated with changes in circulating plasma protein levels analogous to those reported in human diabetic patients with clinical evidence of complications; (b) to evaluate the effects of experimental diabetes on the net cumulative biosynthesis of 10 specific plasma proteins by the isolated liver, perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that the serum levels of α 1 -I III reduced in diabetes, while macroglobulin did not change appreciably in diabetic rats. , The serum Hp concentration in peritoneal dialysis patients with diabetes is lower than that in patients without diabetes, and it is not related to inflammation, nutrition, or adequacy of dialysis . Miller et al tried to elucidate whether protracted diabetes in rats is associated with changes in circulating plasma Hpx levels in rats analogues to those reported in human diabetic patients with clinical evidence of complications. The Vn might be increased from activated platelets in the early stage of diabetic nephropathy .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the serum levels of α 1 -I III reduced in diabetes, while macroglobulin did not change appreciably in diabetic rats. , The serum Hp concentration in peritoneal dialysis patients with diabetes is lower than that in patients without diabetes, and it is not related to inflammation, nutrition, or adequacy of dialysis . Miller et al tried to elucidate whether protracted diabetes in rats is associated with changes in circulating plasma Hpx levels in rats analogues to those reported in human diabetic patients with clinical evidence of complications. The Vn might be increased from activated platelets in the early stage of diabetic nephropathy .…”
Section: Discussionmentioning
confidence: 99%
“…In both alloxan-and streptozotocin-induced diabetic rats, the decrease in insulin level is accompanied by substantial reductions in plasma Cp (73)(74)(75), and treatment of diabetic rats with insulin restores plasma Cp to normal levels (75). Similarly, treatment of rats with streptozotocin decreases Cp synthesis by the isolated perfused liver, but is restored to normal after treatment of the rats with insulin (76). Taken together, these data suggest a possible regulatory activity of insulin on hepatic Cp synthesis and Cp plasma concentration in vivo.…”
Section: Induction Of Cp Expression Bymentioning
confidence: 99%
“…Chen et al has reported upregulation of Hpx in plasma of human subjects with T1DM due to glucose‐induced oxidative stress. However, Miller et al demonstrated that the plasma level of Hpx in STZ‐induced diabetic rats was reduced to 75% that of normal rats. Hpx serves as the major vehicle for transportation of heme in the plasma by scavenging the heme released or lost due to turnover of heme proteins such as hemoglobin, thus protecting the body from oxidative damage induced by free heme .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [8] has reported upregulation of Hpx in plasma of human subjects with T1DM due to glucose-induced oxidative stress. However, Miller et al [50] demonstrated that the plasma level of Hpx in STZ-induced A B Table 1.…”
mentioning
confidence: 99%